Rosiglitazone attenuates liver inflammation in a rat model of nonalcoholic steatohepatitis - ÇELİKEL, ÇİĞDEM; YAVUZ, DİLEK; EREN, FATİH; HAKLAR, GONCAGÜL; YÜKSEL, MERAL (SPRINGER, 2007)
Rosiglitazone is an insulin-sensitizing agent. We aimed to assess the effects of rosiglitazone on a methionine- and choline-deficient diet (MCDD) model of nonalcoholic steatohepatitis (NASH) in rats. Wistar rats were fed either MCDD or a control diet in the 4-week induction study; they were given saline or 4 mg/kg/day rosiglitazone. After the induction study period, the rats were divided into four groups and fed MCDD or given a control diet for an additional 8 weeks and received saline or rosiglitazone. Serum and tissue samples were obtained. Rosiglitazone improved inflammation in NASH and improved ALT, alkaline phosphatase, and interleukin-6 levels in the induction study and interleukin-1 beta, interleukin-6, and tumor necrosis factor-alpha levels in the treatment study. Our preliminary study is the first to show the anti-inflammatory effects of rosiglitazone in NASH. Rosiglitazone's effect on cytokines may be a key mechanism of its anti-inflammatory effect in NASH.
Keywords: rosiglitazone; insulin resistance; nonalcoholic fatty liver disease; oral glucose tolerance test; reactive oxygen species; cytokine; interleukin; tumor necrosis factor; GAMMA LIGAND ROSIGLITAZONE; STELLATE CELL ACTIVATION; CHOLINE-DEFICIENT DIET; INSULIN SENSITIVITY; HEPATIC STEATOSIS; REACTIVE OXYGEN; RECEPTOR-GAMMA; TROGLITAZONE; METHIONINE; TRIGLYCERIDE